PROBLEMATIKA PEMBELAJARAN MENULIS PERMULAAN PADA SISWA SEKOLAH DASAR - Kodrat Hi. Karim (PEDAGOGIK, 2014)
The study was conducted to address the problems experienced by low-grade student in a writing activity. The research conducted a grade one and two SD Alkhairaat 04 of Ternate. The  method used  descriptive qualitative.  The  data collected questionnaire, interviews, observation  and  documentation  Data  analysis  used  qualitative  analysis.  The  results showed the difficulties experienced by the first graders among others, (a) writing letters, words and simple sentences, (b) write the letter continued, (c) write the sentence correctly, (d) to distinguish the letters b and d (often confused ), (e) hard imitating or copying written form provided by the teacher (f) it is difficult to string words into simple sentences. While the second graders have difficulty writing in terms of: (a) writing letters, words and simple sentences with a clear, (b) write a sentence correctly and appropriately in accordance with the teacher delivered, (c) write and use the letters continued, and (d) have not been able to recognize and understand the function of punctuation correctly, such as commas and periods, use of capital letters. and it is hard to maintain the neatness and the written form. Key words: writing problem, the beginer students.